The Acquisition of Simple Sentence Spoken: Case Study Of Belva Razita Maghribi - Tias Sil Romansyah; Hidayana Putri; Abdul Rahmad (Jurnal Edukasi Terkini, 2025)
Purpose-The main objective of this research is analyzed about how a seven years old child that is a subject of this research acquires simple sentences spoken and to identify the factors affected in acquiring simple sentences acquisition. Research Methodology / Design / Approach-The current study adheres to the qualitative method, and its data collected via natural observations and face-to-face interviews with a seven years old child selected purposively. Finding-Result showed that the factors of the acquisition on simple sentence spoken are affected by exposure of English language, interaction with family members, occupation of the subject’s parents, and the willingness of the subject to learn English. Originality/Value- In addition, the processes of the subject in acquiring simple sentence spoken are the subject can answer the questions fluently with correct pronunciation, the subject efforts’ in answering the questions directly, and the subject utterances the simple English sentence is understandable. It also showed that the subject familiar in question form of demonstrative pronouns this and that.